The impact of trade agreements on consumer welfare: evidence from the European Union's common external trade policy - Berlingieri, Giuseppe; Breinlich, Holger; Dhingra, Swati (Wiley, 2018)
This paper estimates the consumer welfare impact of the new generation of trade agreements implemented by the European Union between 1993 and 2013. We decompose the overall effect into contributions of changes in prices, quality and variety. Estimating trade elasticities for narrow product categories of EU imports, we infer quality from data on imported values and volumes. For the EU as a whole, we find that trade agreements increased quality by 7% on average but did not affect prices or variety. This translates into a cumulative reduction in the consumer price index of 0.24% over our sample period. We also find a high degree of impact heterogeneity across EU countries, trading partners and the type of trade agreement, with high-income EU countries seeing much stronger quality increases and larger overall consumer benefits.